2016
DOI: 10.1111/jocn.13288
|View full text |Cite
|
Sign up to set email alerts
|

Building resilience in the face of adversity: navigation processes used by older lesbian, gay, bisexual and transgender adults living in Ireland

Abstract: Nurses not only need to be aware of the life histories of older lesbian, gay, bisexual and transgender people but they also need to assess their strengths and offer sensitive services that promote and support resilience among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…Consequently, older LGBT+ people have significant fears around accessing health and social care services (Brotman et al 2003;Hughes, 2009;Sharek et al 2015). Health and social care systems are viewed as unwelcoming for older LGBT+ people (McFarland & Sanders, 2003;Shankle et al 2003), with many expressing concerns around discrimination in residential care services (Johnson et al 2005) as well as concerns around not having their needs met (Higgins et al 2016;Glackin and Higgins, 2008).…”
Section: Pedagogical Principles and Methods Underpinning Education Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, older LGBT+ people have significant fears around accessing health and social care services (Brotman et al 2003;Hughes, 2009;Sharek et al 2015). Health and social care systems are viewed as unwelcoming for older LGBT+ people (McFarland & Sanders, 2003;Shankle et al 2003), with many expressing concerns around discrimination in residential care services (Johnson et al 2005) as well as concerns around not having their needs met (Higgins et al 2016;Glackin and Higgins, 2008).…”
Section: Pedagogical Principles and Methods Underpinning Education Ofmentioning
confidence: 99%
“…Several authors have concluded that LGBT+ competency training is needed in services that provide affirmative and gender sensitive care to older LGBT+ people (Bell et al 2010;Higgins et al 2016;Hughes et al 2011;Knochel et al 2011;Stein et al 2010). Research suggests that specific training on issues facing older LGBT+ people may result in better knowledge/skills of the health and social care workforce, which in turn may reduce the heteronormative and cisgendered communication between providers and LGBT+ people, as well as diminish feelings of stigma and discrimination experienced by LGTB+ people (Sekoni et al 2017).…”
Section: Pedagogical Principles and Methods Underpinning Education Ofmentioning
confidence: 99%
“…Lack of inclusive care has been linked to conflicting religious and cultural beliefs (Barnes and Meyer, 2012;Brown and Cocker, 2011), to ageist attitudes in relation to sexuality and ageing (Gewirtz-Meydan et al 2018;Cook, Schouton and Henrickson, 2018) and a lack of awareness of the need to tailor health and social care, particularly within care homes (Simpson, Almack and Walthery, 2018;Willis et al, 2018;Hafford-Letchfield et al, 2018). The provision of affirmative care for LGBT+ older people has been firmly linked to the need for awareness and targeted education and training supported by policies and benchmarking standards (Bell et al 2010;Higgins et al 2016;Hughes, Harold and Boyer. 2011;Knochel, Quam and Croghan.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the literature suggests that adversity and trauma can lead individuals to be more “tuned into” the suffering of others (Greenberg, Baron‐Cohen, Rosenberg, Fonagy, & Rentfrow, 2018; Piff, Kraus, Côté, Cheng, & Keltner, 2010; Rose, 2017; Seery, Holman, & Silver, 2010; van Kleef et al, 2008), increasing one's motivation to alleviate those other persons' suffering, described in the model known as “empathetic prosocial growth” (Lim & DeSteno, 2016; Vollhardt & Staub, 2011). The discrimination that LGB+ persons face on a daily basis is also a form of adversity (Higgins, Sharek, & Glacken, 2016; Schmidt, Miles, & Welsh, 2011) and thus such individuals are also likely more empathetic and tuned to the needs of others in similar predicaments.…”
mentioning
confidence: 99%